Evaluating the Impact of a Teaching Program on Nurses' Performance during CVP Measurement in Intensive Care Units: A Quasi-Experimental Study - Abu Jaish, Yasser Adnan (European Scientific Journal, ESJ, 2023)
The intensive care unit (ICU) is a specialized area of hospitals dealing with the diagnosis, management, and follow-up of critically ill patients. Moreover, Critical Care Nurses (CCNs) should have strong analytical, interpersonal, and decision-making skills. Objectives: This study aimed to assess the effect of the teaching program on CCNs’ performance during the measurement of central venous pressure (CVP). Design: A quasi-experimental design was used. Methods: The study was conducted in the critical care units at Al-Assad University Hospital, Damascus from June to September 2020. All available registered nurses working in the previous ICUs were included. An observational checklist sheet was developed by the researcher after reviewing the related literature. Each nurse was observed once for each procedure during different shifts. The researcher developed and designed the teaching program based on the nurses’ needs according to their performance during the initial assessment. Results: The results showed that the performance of the nurses improved after the program. The best performance was for nurses in the age group between 20 and 24 years, nurses with a master’s degree, and nurses with less than five years of experience, while the level of knowledge and practice of the studied nurses was average and poor before the teaching program. Overall, this study found a statistically significant relationship before and after the implementation of the program. Conclusion: There has been an obvious improvement in nurses’ knowledge and performance after the teaching program. It is essential to help nurses expand their knowledge and practices to provide high-quality care and promote patient safety.